A droplet‐based electricity generator with ultrahigh instantaneous output and short charging time. Issue 1 (25th July 2022) - Zhang, Nan; Zhang, Huimin; Xu, Wanghuai; Gu, Haojie; Ye, Shimeng; Zheng, Huanxi; Song, Yuxin; Wang, Zuankai; Zhou, Xiaofeng
Abstract: The past several years have witnessed the rapid development in effectively transforming randomly distributed water kinetic energy into electrical energy, especially triggered by the emergence of droplet‐based electricity generators (DEG). Despite this, it still suffers from relatively low average power density, which is also achieved at the cost of long charging time, the time to reach stable and saturated surface charge density either through continuous droplet impingement or precharging. Although the harvested energy per droplet in DEG remains as the dominant metric, ultrahigh instantaneous output and short charging time are equally important in some specialized applications such as instantaneous luminescence. Here, we conduct systematical modeling and optimization to build the link between the hydrodynamic and electrical systems, which enables us to determine ultrahigh instantaneous output and short charging time by tailoring parameters such as dielectric layer thickness, droplet ion concentration, and external load. We envision that this strategy in achieving ultrahigh instantaneous output as well as shortening charging time would provide insights and design routes for water energy harvesting. Abstract : This study is to formulate a fundamental framework to dramatically boost the instantaneous output of droplet‐based electricity generators and reduce the charging time by systematically modeling and optimizing the hydrodynamic and circuit systems.